2022
DOI: 10.1109/access.2022.3201560
|View full text |Cite
|
Sign up to set email alerts
|

DeblurGAN-CNN: Effective Image Denoising and Recognition for Noisy Handwritten Characters

Abstract: Many problems can reduce handwritten character recognition performance, such as image degradation, light conditions, low-resolution images, and even the quality of the capture devices. However, in this research, we have focused on the noise in the character images that could decrease the accuracy of handwritten character recognition. Many types of noise penalties influence the recognition performance, for example, low resolution, Gaussian noise, low contrast, and blur. First, this research proposes a method th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…The suggested model outperforms the conventional DL method, which relies on the unweighted model average (UMA) and majority voting (MV) by a profit of 31.25%. This follows the reasoning of Gonwirat and Surinta [ 91 ], who similarly concluded that metaheuristics, such as AMIS, can enhance the quality of solutions obtained using DLs employing the conventional UMA and MV.…”
Section: Discussionsupporting
confidence: 73%
“…The suggested model outperforms the conventional DL method, which relies on the unweighted model average (UMA) and majority voting (MV) by a profit of 31.25%. This follows the reasoning of Gonwirat and Surinta [ 91 ], who similarly concluded that metaheuristics, such as AMIS, can enhance the quality of solutions obtained using DLs employing the conventional UMA and MV.…”
Section: Discussionsupporting
confidence: 73%
“…The decision fusion strategy is the reason for the significantly higher performance of our proposed model. Our methodology and its results are supported by [43,45,65,66].…”
Section: Discussionsupporting
confidence: 59%
“…We separated the total dataset into a training set and a test set with proportions of 80% and 20%, having 5606 training images and 1408 test images. Consequently, the training set was tested utilizing five-fold cross-validation [ 50 , 51 ]. The test set served as a separate holdover for final evaluation.…”
Section: Resultsmentioning
confidence: 99%